ENG 110 - Introduction to Film Studies - Stephen Rust (Linn-Benton Community College, 2021)
This is a Canvas Course that provides lectures, assignments, and other resources built around the OER textbook, Moving Pictures (https://open.umn.edu/opentextbooks/textbooks/804). People respond to movies in different ways, and there are many reasons for this. We have all stood in the lobby of a theater and heard conflicting opinions from people who have just seen the same film. Some loved it, some hated it, some found it just OK. Disagreements, however, can reveal a great deal about the assumptions underlying these various responses. In this course we will see that there are many ways of thinking about movies and approaches that we can use to analyze them. We will cover key aspects of film criticism, theory, and history in the spirit of intellectual investigation of visual culture. Overall, the goal of this course is to introduce you to the basic skills necessary for a critical knowledge of the movies as art, culture, and industry.